The spatial multidimensionality of sectoral innovation: the case of information and communication technologies - Knut Koschatzky; Elisabeth Baier; Henning Kroll; Thomas Stahlecker (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2009)
The innovation system approach has become a current and frequently used tool for the assessment of innovative activities in different fields of study. So far, however, there is no unanimous agreement on the issue of the most relevant perspective which has to be taken when applying the approach to the study of individual cases - the territorial or the sectoral. This paper argues that it is both unlikely and analytically undesirable that any one of them should prevail. We will point out that taking the ICT sector as a case study, in most cases both territorial and sectoral determinants influence the develop-ment of innovative activities. We thus argue that neither the sectoral perspective can be thought of without taking into account territorial framework conditions nor vice versa. Even when the individual academic undertaking requires lying emphasis on one of the perspectives, the other needs to be included in the analysis.
urn:nbn:de:0011-n-971222
Keywords: 330; Innovation; Branchenentwicklung; Standortfaktor; IT-Industrie; Wien; Baden-Württemberg; Finnland